2012
DOI: 10.1002/hed.23137
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and functional outcome of the preserved eye in malignant sinonasal tumors

Abstract: Adequate local control with preserved visual function can be obtained with surgery and adjuvant radiation in appropriately selected malignant sinonasal tumors with orbital involvement. The preserved eye, if reconstructed appropriately, maintains good overall function with acceptable morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
5
17
0
1
Order By: Relevance
“…The rate of local recurrence was quite comparable at 30% in the orbital preservation group and 33% in the orbital exenteration group. Rajapurkar et al . further showed that orbital preservation can be performed in cases with limited periorbital and orbital soft tissue involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of local recurrence was quite comparable at 30% in the orbital preservation group and 33% in the orbital exenteration group. Rajapurkar et al . further showed that orbital preservation can be performed in cases with limited periorbital and orbital soft tissue involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative ophthalmologic exam along with computed tomography (CT) imaging and magnetic resonance imaging (MRI) can help delineate the extent of involvement beyond the periorbita . Recent data suggests that tumors which have limited periorbital involvement and do not invade into the orbital fat, extraocular muscles, or optic nerve can be technically resected, while preserving the orbit with satisfactory local control and overall survival rates …”
mentioning
confidence: 99%
“…Dans le cas particulier des tumeurs ayant nécessité une irradiation à proximité des voies optiques (sinus de la face, cavum), une baisse d'acuité visuelle, un déficit campimétrique ou une xérophtalmie peuvent survenir, notamment dans l'année qui suit la radiothérapie [55]. Un suivi ophtalmologique annuel est proposé.…”
Section: Autre Toxicité Radio-induiteunclassified
“…Advanced stage lesions require adjuvant radiotherapy with or without chemotherapy as adjuvant treatment. The overall outcomes of sinonasal malignancies have significantly improved over the years as a consequence of this treatment approach [20]. Craniofacial resection has been considered the gold standard in the treatment of malignancies involving the anterior skull base.…”
Section: Paranasal Sinuses Including Anterior Skull Basementioning
confidence: 99%
“…The indications for preservation of orbital contents during surgical resection of malignant sinonasal tumors invading the orbit remain disputed. The oncological safety of preserving the orbit and the functional outcome of the preserved eye are two factors that are to be considered [20]. Imola and Schramm in their study concluded that eye preservation can be attempted in tumors that invade the orbital soft tissues with penetration through the periorbita provided that it can be easily and completely dissected away from the orbital fat using microscopic control [23].…”
Section: Paranasal Sinuses Including Anterior Skull Basementioning
confidence: 99%